Determinants of Tax Compliance among Individual Business and Freelance Taxpayers: Evidence from KPP Pratama Senapelan Pekanbaru - Sefita Nahdia Syifa; Taufeni Taufik; Atika Zarefar (Jurnal Riset Perpajakan: Amnesty, 2025)
This study investigates the determinants of tax compliance among individual taxpayers engaged in business and freelance activities at the Pratama Tax Office (KPP) of Senapelan, Pekanbaru. The research examines the influence of four key variables—taxation socialization, level of taxation understanding, taxpayer awareness, and tax sanctions—on individual taxpayer compliance. Using a purposive sampling method, 110 respondents were selected based on specific criteria, including registration at the tax office and submission of the Annual Tax Return (SPT) form 1770. Primary data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS version 30. The findings reveal that the level of taxation understanding, taxpayer awareness, and tax sanctions significantly affect tax compliance. In contrast, taxation socialization does not have a statistically significant impact. These results suggest that improved understanding of tax regulations, enhanced civic awareness, and effective enforcement of sanctions play critical roles in increasing taxpayer compliance. However, the lack of impact from socialization programs may be attributed to limited outreach or low participation in tax education activities. The study highlights the need for intensified and targeted educational campaigns by tax authorities to foster compliance, especially among self-employed individuals and freelancers. Additionally, the enforcement of tax sanctions should remain firm and transparent to deter non-compliance. These findings provide practical insights for policymakers and tax administrators in designing more effective compliance strategies. Future research should consider incorporating other potential variables, such as trust in tax institutions, quality of tax services, and digital literacy, to gain a more comprehensive understanding of taxpayer behavior.